Public Service Management: An Emerging Research Trend - Andhika, Lesmana Rian (Jurnal Borneo Administrator, 2025)
Public service management is a way to provide better service to users, increase efficiency, and increase knowledge and experience in public service delivery. This research aims to identify the shift of public service management research focus. The systematic review method decreases bias by identifying, evaluating, and synthesizing relevant studies on a particular topic and making significant contributions to answering the research question. This study demonstrates that public service management research does not rely on creating efficiency and effectiveness through applying private sector business and management techniques, particularly in government agencies. In addition, public sector leadership, partnerships and collaboration, digital transformation, public participation and engagement, and public service delivery are all areas that play significant role to the development of service efficiencies and experiences. Public service is a process that involves various actors, from politicians and bureaucrats to citizens and the private sector. Public service management is critical to ensuring services operate efficiently and effectively and provide public value. The management principles allow the government to focus on service quality, equity, and ease of use. Appropriate public service management can contribute practically to the delivery of public service implemented in government institutions. This is possible by considering the fundamental management principles and research findings that contribute to service development in the future